Therapeutic effects of repetitive transcranial magnetic stimulation on cognitive impairment in stroke patients: a systematic review and meta-analysis - Gong, Cheng; Hu, Hao; Peng, Xu-Miao; Li, Hai; Xiao, Li; Liu, Zhen; Zhong, Yan-Biao; Wang, Mao-Yuan; Luo, Yun (Frontiers in Human Neuroscience, 2023)
Background: In recent years, repetitive transcranial magnetic stimulation (rTMS) has emerged as a noninvasive and painless treatment for post-stroke cognitive impairment (PSCI). However, few studies have analyzed the intervention parameters of cognitive function and the effectiveness and safety of rTMS for treating patients with PSCI. Thus, this meta-analysis aimed to further evaluate the effectiveness and safety of rTMS for treating patients with PSCI. Methods: According to the PRISMA guidelines, we searched the Web of Science, PubMed, EBSCO, Cochrane Library, PEDro, and Embase to retrieve randomized controlled trials (RCTs) of rTMS for the treatment of patients with PSCI. Studies were screened according to the inclusion and exclusion criteria, and two reviewers independently performed literature screening, data extraction, and quality assessment. RevMan 5.40 software was used for data analysis. The size of the I² statistic described the high level of heterogeneity between studies. Results: Ten RCTs involving 453 patients with PSCI met the inclusion criteria. In our analysis, rTMS had a positive therapeutic effect on cognitive rehabilitation in patients with PSCI (P<0.05). Both high-frequency rTMS and low-frequency rTMS effectively improved cognitive function in patients with PSCI, but no statistical difference in their efficacy (P>0.05). Conclusions: Both high-frequency rTMS and low-frequency rTMS are effective in accelerating the improvement of cognitive function in patients with PSCI.